Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1136/annrheumdis-2015-eular.2910
|View full text |Cite
|
Sign up to set email alerts
|

THU0182 Single Dose? Multiple Doses? Comparison of MTX-PG Concentration, Safety and Efficacy in Patients with Rheumadoid Arthritis Between Single- and Divided Dosage Regimens

Abstract: BackgroundMethotrexate (MTX) has been well-known anchor drug for rheumatoid arthritis (RA), however, dose regimen varies and it depends on countries. The divided dosage of MTX was frequently prescribed in Japan, however, the differences of safety and efficacy between divided and single dose regimens were not fully examined.ObjectivesWe conducted a preliminary study for RA patients to compare the safety, efficacy profile and MTX-polyglutamates (PGs) concentration between single- and divided dosage regimens.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The sample size for this study was calculated from the results of a preliminary study conducted under the same target patient conditions as this study, 8 In this preliminary study, liver dysfunction occurred in 3 out of 16 patients in the 3-dose group during the 19-…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The sample size for this study was calculated from the results of a preliminary study conducted under the same target patient conditions as this study, 8 In this preliminary study, liver dysfunction occurred in 3 out of 16 patients in the 3-dose group during the 19-…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the incidence of liver dysfunction was selected as the primary endpoint based on the results of the preliminary study 8 . Although the significant increase in liver enzymes (transaminases) associated with the divided‐dose regimen that was detected in the preliminary study was confirmed, a statistically significant difference in the incidence was not detected between groups.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations